Flexible Soft-Printed Polymer Films with Tunable Plasmonic Properties - Solomonov, Aleksei; Kozell, Anna; Tesler, Alexander; Pinkas, Iddo; Walensky, Seth; Shimanovich, Ulyana (ACS Materials Au, 2023)
Noble metal nanoparticles (NPs) and particularly gold (Au) have become emerging materials in recent decades due to their exceptional optical properties, such as localized surface plasmons. Although multiple and relatively simple protocols have been developed for AuNP synthesis, the functionalization of solid surfaces composed of soft matter with AuNPs often requires complex and multistep processes. Here we developed a facile approach for functionalizing soft adhesive flexible films with plasmonic AuNPs. The synthetic route is based on preparing Au nanoislands (AuNI) (ca. 2-300 nm) on a glass substrate followed by hydrophobization of the functionalized surface, which in turn, allows efficient transfer of AuNIs to flexible adhesive films via soft-printing tape lithography. Here we show that the AuNI structure remained intact after the hydrophobization and soft-printing procedures. The AuNI-functionalized flexible films were characterized by various techniques, revealing unique characteristics such as tunable localized plasmon resonance and Raman enhancement factors beneficial for chemical and biological sensing applications.
CRIS-Team Scopus Importer:2023-09-29
Keywords: gold nanostructures and nanoparticles; plasmonics; SERS; soft printing; solid polymer films; tape lithography